Comprehensive Analysis of Virulence Determinants and Genomic Islands of blaNDM-1-Producing Enterobacter hormaechei Clinical Isolates from Greece - Angeliki Mavroidi; Konstantina Gartzonika; Nick Spanakis; Elisavet Froukala; Christos Kittas; Georgia Vrioni; Athanasios Tsakris (MDPI AG, 2023)
Nosocomial outbreaks of multidrug-resistant (MDR) Enterobacter cloacae complex (ECC) are often reported worldwide, mostly associated with a small number of multilocus-sequence types of E. hormaechei and E. cloacae strains. In Europe, the largest clonal outbreak of blaNDM-1-producing ECC has been recently reported, involving an ST182 E. hormaechei strain in a Greek teaching hospital. In the current study, we aimed to further investigate the genetic make-up of two representative outbreak isolates. Comparative genomics of whole genome sequences (WGS) was performed, including whole genome-based taxonomic analysis and in silico prediction of virulence determinants of the bacterial cell surface, plasmids, antibiotic resistance genes and virulence factors present on genomic islands. The enterobacterial common antigen and the colanic antigen of the cell surface were identified in both isolates, being similar to the gene clusters of the E. hormaechei ATCC 49162 and E. cloacae ATCC 13047 type strains, whereas the two strains possessed different gene clusters encoding lipopolysaccharide O-antigens. Other virulence factors of the bacterial cell surface, such as flagella, fimbriae and pili, were also predicted to be encoded by gene clusters similar to those found in Enterobacter spp. and other Enterobacterales. Secretion systems and toxin-antitoxin systems, which also contribute to pathogenicity, were identified. Both isolates harboured resistance genes to multiple antimicrobial classes, including β-lactams, aminoglycosides, quinolones, chloramphenicol, trimethoprim, sulfonamides and fosfomycin; they carried blaTEM-1, blaOXA-1, blaNDM-1, and one of them also carried blaCTXM-14, blaCTXM-15 and blaLAP-2 plasmidic alleles. Our comprehensive analysis of the WGS assemblies revealed that blaNDM-1-producing outbreak isolates possess components of the bacterial cell surface as well as genomic islands, harbouring resistance genes to several antimicrobial classes and various virulence factors. Differences in the plasmids carrying β-lactamase genes between the two strains have also shown diverse modes of acquisition and an ongoing evolution of these mobile elements.